L’incontro con lo straniero alla luce della filosofia di Panikkar - Torrero, Claudio Giuseppe (Filosofia, 2015)
Raimon Panikkar is the eminent philosopher and theologian who integra- ted Hinduism and Buddhism into his Christian faith, considering each religion as a language that can be translated into other languages, and the different traditions as streams that flow into the river of one’s spiritual experience. He rediscovered an original meaning of philosophy in India, which was lost in Western thought, as inseparable from the spiritual quest. In particular, he stated that Buddhism ma- naged to unburden the Indian culture from the identification of God with Being, and of Being with human thought, a perspective that has been central to Western philosophy and has made modern atheism inevitable. In our time we are probably witnessing an event analogous to that which happened when Buddhism arose. We can resort to modern atheism as a way to freedom but only if we can prevent Man from taking God’s place. In this way, and in this way only, can we unlock the gates to Grace.